The Effect Of Brand Awareness, Promotion On Purchase Decision With Customer Satisfaction As A Moderation Variable study on shopee users at Muhammadiyah 5 Karanggeneng High School) - Yuliana Tri Ratnasari; Muhammad Dzikri A; Siti Musarofah; Didik Puji Wahyono (Cita konsultindo, 2023)
This study aims to test and analyze the influence of brand awareness, promotion on purchasing decisions with consumer satisfaction as a moderation variable (study on shopee users at SMA Muhammadiyah 5 Karanggeneng). The research sample was 125 students using non-probability sampling techniques. This type of research is quantitative research. The data was processed statistically using the SPSS for windows version 26 program. The results of the study based on respondents' responses show that brand awareness has a significant effect on purchasing decisions. This means that shopee e-commerce brand awareness can improve consumer purchase decisions. Promotion has a significant effect on purchasing decisions. This means that shopee promotions can improve purchase decisions. Persial Consumer satisfaction has a significant effect on purchasing decisions This means that shopee consumer satisfaction can improve purchase decisions. Consumer satisfaction does not moderate brand awareness of purchasing decisions. Consumer satisfaction does not moderate promotions against purchase decisions.